solving systems of equations by substitution y= -4/9x -3

y =-7/5x-3

y= -4/9x -3

-4/9x -3 =-7/5x-3

by looking at the problem you can see that you will end up with a number times x equal to zero. when you divide by that number to get x, you know that ant number divided by 0 is 0.

x=0

2. replace x with zero

y= -4/9(0) -3

y=-3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up